Optimalisasi Asesmen Psikologi dalam Layanan Konseling : Bentuk, Tujuan, dan Implementasinya - Mohammad Danar Zila Saputra (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This study discusses the role of assessment in guidance and counseling services, particularly how assessment assists counselors in understanding clients and the types of assessments commonly used in the counseling process. Assessment is a crucial tool for gathering objective and comprehensive data about clients’ potentials, problems, and psychological conditions. Through test and non-test assessment techniques, counselors can obtain a thorough overview that supports the development of targeted service programs. This study emphasizes that the selection of assessment types should be adjusted to the client’s needs and characteristics to ensure effective counseling. Assessments not only provide data for planning but also contribute to client self-understanding, increase motivation for change, and help identify obstacles that need to be addressed. Therefore, the ethical and professional application of assessment is essential in supporting the success of guidance and counseling services.